The Role of Financial Literacy in Preventing Fraudulent Investments in Bengkulu: A Case Study of Central Bengkulu - Anggun Citra Lestari; Masnita Sinaga; Ilham Rudiansyah; Arya Sulistio Setiawan (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2025)
Financial fraud has become an increasing concern in Indonesia, particularly in smaller regions such as Central Bengkulu. The rapid expansion of online investment platforms and limited understanding of financial principles have made the local population vulnerable to fraudulent investment schemes. This study aims to analyze the role of financial literacy in preventing individuals from engaging in such deceptive investment activities. Using a qualitative descriptive approach, data were collected through semi-structured interviews and documentation from ten participants in Central Bengkulu who had prior experience or knowledge related to investment. The findings reveal that individuals with higher financial literacy demonstrate stronger awareness of risk assessment, greater ability to verify financial information, and are less likely to be deceived by unrealistic promises of high returns. Conversely, low levels of financial understanding correlate with susceptibility to fraudulent investment offers. The study concludes that strengthening financial literacy through community education, government initiatives, and digital literacy programs can significantly reduce the risk of financial fraud in local communities